Biochemical markers of the functional disorders of the liver in patients with systemic lupus erythematosus - L.F. Bogmat; N.S. Shevchenko; I.N. Bessonova; V.V. Nikonova; E.L. Akhnazaryants (Zaslavsky O.Yu., 2017)
Background. Systemic lupus erythematosus (SLE) in the basis of the pathogenesis has generalized autoimmune inflammation, which leads to the development of a wide range of immune-inflammatory organ disorders. Among them, the liver deserves special attention, since its functional state can reflect not only the severity of the pathological process, but also the response on aggressive treatment. The purpose of the work was studying the biochemical markers of the functional state of the liver in children with initial stages of SLE. Materials and methods. Features of the lipid, carbohydrate spectrum of the blood, indicators of pigment exchange, markers of cytolysis, cholestasis, fibrosis and protein-synthetic function of the liver were studied in children and adolescents with SLE. Twenty six patients aged 7-18 years were examined. Two groups were formed: 10 patients (38.4 %) with the duration of the disease of 1-3 years and 16 people (61.5 %) with duration of more than 3 years. Results. The average blood lipids levels did not exceed the reference values and did not have statistical differences among the patients of the selected groups. The levels of total cholesterol and triglycerides in both groups of patients significantly exceeded the control values (p < 0.05). Indicators of low density lipoprotein cholesterol increased already in the early stages of the disease (p < 0.05) and reached the maximum values in individuals with a course of SLE over 3 years (p < 0.05). Concentration of high density lipoprotein cholesterol in patients of the second group decreased somewhat (p < 0.1). There was an increase in the average values of atherogenic index by 1.7 times among patients in the first group (p < 0.05) and 2.25 times in persons from the second group (p < 0.05). Studies of other metabolic links showed that the average values of glycaemia and immunoreactive insulin (IRI) were consistent with the physiological norm. However, half of patients with SLE had hyperinsulinaemia (an increase in IRI of more than 25 μM/ml). There is a tendency to disturbance of pigmentary metabolism. The average total bilirubin values increased with an increase in the duration of the disease (p < 0.05) and depending on the activity of the disease (r = 0.632; p < 0.05). With the duration of SLE over 3 years, the concentration of haptoglobin significantly decreased (1.1 ± 0.1 g/l against 1.6 ± 0.2 g/l, p < 0.05), and there were high concentrations of AST (in 12.5 % of the surveyed persons). The growth in the parameters of fibrosis formation has been established; p < 0.05. Conclusions. In children suffering from SLE, already in the early stages there are significant changes in the functional state of the liver. The presence of atherogenic dyslipidemia was detected, which deepened with increasing duration and activity of the disease. 50.0 % of the subjects have a violation of carbohydrate metabolism in the form of hyperinsulinemia. A decrease in the concentration of hapthoglobin, as well as the association of liver fibrosis indeces AST/PYP and ALT/PYR, depended on the duration and activity of the disease.